Climate change and population connectivity of Lakshadweep atolls - Athira Prasad (Academy of Climate Change Education and Research, 2018)
Lakshadweep is the only atoll type reefs in the territory of India. Since Indian Ocean is the warmest among tropical oceans, Indian corals reefs are vulnerable to the impact of climate change. Coral connectivity helps in maintaining the resilience capacity of sensitive coral reefs. However, shifts in global temperature will strongly influence the period of larval duration and hence the connectivity between the reefs. This study utilised the Mann Kendall trend analysis and Empirical Orthogonal Formula to study the trend of sea surface temperature and salinity over the region. Current study revealed a warming trend of sea surface temperature of Lakshadweep waters. Empirical orthogonal function indicates opposite temperature and salinity modes in the Indian Ocean region which encompasses the Lakshadweep waters. Spatio temporal dipoles identified are surmised to be due to the influence of global climatic phenomenon like El Niño and Indian Ocean Dipole. The study also tries to understand the relationship between larval connectivity and climate. Our findings implies that climate change has a significant influence on larvae and in turn affecting the journey to their corresponding settlement reef. Resilient reefs act as the source for seeding the bleached or destroyed reefs by larval dispersal. Knowledge on the changes of larval connectivity between the reefs can help in taking important decisions during the interpretation and implementation of resilience based management tools in a coral reef. Identifying the pattern of settlement and population connectivity supports in making new Marine Protected areas.